2011
DOI: 10.1111/j.1530-0277.2011.01512.x
|View full text |Cite
|
Sign up to set email alerts
|

Dissociation Between Affective and Cognitive Empathy in Alcoholism: A Specific Deficit for the Emotional Dimension

Abstract: At the theoretical level, this first observation of a specific deficit for emotional empathy in alcoholism, combined with the exact inverse pattern observed in other psychiatric populations, leads to a double-dissociation, which supports the notion that emotional and cognitive empathy are 2 distinct abilities. At the clinical level, this deficit calls for considering emotional empathy rehabilitation as a crucial concern in psychotherapy. Background: Emotional impairments constitute a crucial and widely describ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
98
1
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 86 publications
(108 citation statements)
references
References 37 publications
7
98
1
2
Order By: Relevance
“…Therefore, it is possible that the dissociation of empathy types is a feature of empathic processing in adolescents with psychiatric disorders in general, rather than those with BPD specifically. This possibility is bolstered by findings of discrepancies across affective and cognitive empathy in other psychiatric disorders (Dziobek et al, 2011;Maurage et al, 2011;Shamay-Tsoory et al, 2007) and evidence of the existence of two neurobiological systems for empathy: a basic emotional contagion system, and a more advanced cognitive perspective-taking system (Shamay-Tsoory et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is possible that the dissociation of empathy types is a feature of empathic processing in adolescents with psychiatric disorders in general, rather than those with BPD specifically. This possibility is bolstered by findings of discrepancies across affective and cognitive empathy in other psychiatric disorders (Dziobek et al, 2011;Maurage et al, 2011;Shamay-Tsoory et al, 2007) and evidence of the existence of two neurobiological systems for empathy: a basic emotional contagion system, and a more advanced cognitive perspective-taking system (Shamay-Tsoory et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…The alcoholics also had lower emotional intelligence scores, suggesting that these factors contributed to impaired interpersonal functioning. Further, higher levels of alexithymia, characterized by difficulties identifying, differentiating, and expressing feelings, have been reported in alcoholism (Maurage et al, 2011; Stasiewicz et al, 2012), and positive correlations between alexithymia measures and severity of alcohol use have been reported (Thorberg et al, 2011). …”
Section: The Five Functional Domainsmentioning
confidence: 99%
“…This confirmed that the affective deficit extends beyond basic emotional states. Other studies have described, on the basis of questionnaires or experimental tasks, deficits in a wide range of emotional abilities such as empathy,30,31 alexithymia,32 or irony detection,33 leading to the proposal of a wide affective processing deficit in ADI.…”
Section: Beyond Efe Recognition: Affective Abilities and Social Cognimentioning
confidence: 99%